Development of Islamic Religious Education at The University - Syahrullah; Attabik Lutfi (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
Islamic religious education in higher education occupies a key position in shaping the personality of the nation's children, as well as functionally integrating it with various disciplines or other fields of study taught in higher education. The reality in the field still shows that there are problems that need to be resolved, such as the formation of attitudes and behavior to respond to the developments and challenges of the times, strengthening the quality of materials, and learning models of Islamic religious education. Islamic education has an important role in character building and is expected to be able to compensate for the ignorance and lack of understanding of students about Islam. Until now, the condition of Islamic religious education in higher education is still far from expectations. This research uses various approaches, there are empirical (ex post facto), and phenomenological approaches that require critical analysis. This study aims to analyze the learning process of Islamic religious education/dirasah Islamiyah in tertiary institutions and explain the study of phenomena that describe the facts of learning development.